CO2 Absorption on Cu-Doped Graphene, a DFT Study - Juan Oseas López Fuentes; Roxana Mitzayé del Castillo Vázquez; Juan Manuel Ramirez-de-Arellano (Crystals)
We studied the interaction between a Cu-doped graphene layer and a CO2 molecule, using DFT, ab initio calculations, and the pseudopotential formalism. We used the Quantum ESPRESSO code package, with the PBE XC functional expression and the semiempirical Grimme’s DFT-D3 Van der Waals correction. We found that the Cu atom, being absorbed in a C vacancy on the graphene surface, has a catalytic effect on the absorption of CO2 in said surface. The Van der Waals correction calculations showed that the CO2 is physisorbed, with an adsorption energy of −0.1786 eV. Our results are congruent with previously published results. The Cu-doped graphene surface could be suitable for the development of a CO2 sensor.